Program Pembinaan Tim Bola Voli di Sekolah Menengah Kejuruan Panjatek Kota Bekasi - Zulham Akbar; Dinda Lestari; Bujang; Naufal Muzzaki (Interdisciplinary Explorations in Research Journal, 2024)
Volleyball team coaching program in Vocational High Schools (SMK) plays an important role in developing athlete skills and shaping student character. Although volleyball is one of the popular sports in Indonesia, many schools do not yet have a systematic and structured coaching program. This study aims to implement and evaluate the volleyball team coaching program at SMK Panjatek to improve students' technical skills, teamwork, and champion mentality. This program was implemented for 3 months with a training frequency of 3 times a week. The evaluation results showed a significant increase in technical skills such as passing, serving, smashing, and blocking, as well as an increase in teamwork and player mentality. This program also succeeded in improving the discipline, communication, and self-confidence of the players. Therefore, this volleyball team coaching program can be used as a model for developing volleyball teams in other schools.